2018
DOI: 10.22603/ssrr.2017-0057
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Postoperative Ileus after Scoliosis Surgery

Abstract: Introduction: One complication after scoliosis surgery is ileus; however, few reports have described the frequency of and risk factors for this complication. We conducted a retrospective clinical study with logistic regression analysis to confirm the frequency of and risk factors for ileus after scoliosis surgery. Methods: After a retrospective review of data from patients who underwent surgical correction of spinal deformity from 2009 to 2014, 110 cases (age range, 4-73 yr; median, 14 yr) were included in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“… 10 , 17 , 18 In particular, ASD surgery has many risk factors that have been reported for POI development, such as use of an anterior approach, surgery in the prone position, scoliosis surgery and intraoperative opioid exposure. 10 , 11 , 19 - 21 A recent study reported a high incidence (18.4%) of POI, and length of stay remains significantly longer in patients who develop POI after adult spinal surgery. 22 However, there was insufficient evidence regarding the risk of development of POI after ASD surgery and the changes in spinal alignment caused by spinal corrective surgery.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 17 , 18 In particular, ASD surgery has many risk factors that have been reported for POI development, such as use of an anterior approach, surgery in the prone position, scoliosis surgery and intraoperative opioid exposure. 10 , 11 , 19 - 21 A recent study reported a high incidence (18.4%) of POI, and length of stay remains significantly longer in patients who develop POI after adult spinal surgery. 22 However, there was insufficient evidence regarding the risk of development of POI after ASD surgery and the changes in spinal alignment caused by spinal corrective surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies analyzing risk factors for a postoperative ileus were able to show that surgical factors such as duration of surgery, selected approach and blood loss might be an important factor in the development of a postoperative ileus. 21,22 Our study did show significant differences between the 2 groups in the length of stay, lumbar surgery and major spine surgery (> 3 level). These results are in line with the study reported by Fineberg et al which identified 7,741 cases of postoperative ileus out of 220 522 lumbar fusions using the NIS (Nationwide Inpatient Sample) data.…”
Section: Discussionmentioning
confidence: 53%
“…Ileus was the second most common complication in the current study, but few reports have described this complication. One retrospective study showed that ileus after scoliosis surgery occurred in 13.6% of patients 28) . Another study showed that paralytic ileus occurred in 6.0% of patients with neuromuscular scoliosis 29) .…”
Section: Discussionmentioning
confidence: 99%